2020
DOI: 10.1080/13625187.2020.1792877
|View full text |Cite
|
Sign up to set email alerts
|

What are the social correlates of subsequent abortions in Flanders, Belgium?

Abstract: Objective: To study whether the social correlates of subsequent abortions vary depending on the order of the abortion.Methodology: Drawing upon the Flemish abortion centers' anonymized patient records (2010-2019), discrete-time hazard models were used to examine whether individual abortion experiences across women's reproductive life course have different social correlates.Results: Overall, women who were in their twenties, of foreign origin, single, had non-tertiary education, were not in paid employment, had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
2
0
0
Order By: Relevance
“…Having denying or irresponsible partner is more related with unstable relationship status and being unmarried. This nding is related with previous studies done in Kenya and Belgium which reported marital status is closely associated with repeat induced abortion; and unmarried women have increased risk of having multiple abortion (22,23). Previous study conducted in Ethiopia and Tunisia also found that being unmarried and separated from husband (being single) are main reasons to undergo multiple termination of pregnancy (14,16,18).…”
Section: Discussionsupporting
confidence: 78%
“…Having denying or irresponsible partner is more related with unstable relationship status and being unmarried. This nding is related with previous studies done in Kenya and Belgium which reported marital status is closely associated with repeat induced abortion; and unmarried women have increased risk of having multiple abortion (22,23). Previous study conducted in Ethiopia and Tunisia also found that being unmarried and separated from husband (being single) are main reasons to undergo multiple termination of pregnancy (14,16,18).…”
Section: Discussionsupporting
confidence: 78%
“…This nding is related with previous studies done in Kenya and Belgium which reported marital status is closely associated with repeat induced abortion; and unmarried women have increased risk of having multiple abortion (22,23). Previous study conducted in Ethiopia and Tunisia also found that being unmarried and separated from husband (being single) are main reasons to undergo multiple termination of pregnancy (14,16,18).…”
Section: Discussionsupporting
confidence: 78%